Memory CD8+ T cells colocalize with IL‐7+ stromal cells in bone marrow and rest in terms of proliferation and transcription. Issue 4 (27th February 2015) - Sercan Alp, Özen; Durlanik, Sibel; Schulz, Daniel; McGrath, Mairi; Grün, Joachim R.; Bardua, Marcus; Ikuta, Koichi; Sgouroudis, Evridiki; Riedel, René; Zehentmeier, Sandra; Hauser, Anja E.; Tsuneto, Motokazu; et al.
<x xml:space="preserve">Abstract</x> It is believed that memory CD8+ T cells are maintained in secondary lymphoid tissues, peripheral tissues, and BM by homeostatic proliferation. Their survival has been shown to be dependent on IL‐7, but it is unclear where they acquire it. Here we show that in murine BM, memory CD8+ T cells individually colocalize with IL‐7+ reticular stromal cells. The T cells are resting in terms of global transcription and do not express markers of activation, for example, 4‐1BB (CD137), IL‐2, or IFN‐γ, despite the expression of CD69 on about 30% of the cells. Ninety‐five percent of the memory CD8+ T cells in BM are in G0 phase of cell cycle and do not express Ki‐67. Less than 1% is in S/M/G2 of cell cycle, according to propidium iodide staining. While previous publications have estimated the extent of proliferation of CD8+ memory T cells on the basis of BrdU incorporation, we show here that BrdU itself induces proliferation of CD8+ memory T cells. Taken together, the present results suggest that CD8+ memory T cells are maintained as resting cells in the BM in dedicated niches with their survival conditional on IL‐7 receptor signaling.